2001
DOI: 10.1097/00006982-200102000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Immune Recovery Vitritis and Uveitis in Aids

Abstract: Symptomatic IRV or IRU develops in a significant number of patients with CMV retinitis following successful HAART. Eyes with CMV surface area >30% of the retina are at the greatest risk. Eyes with IRV respond favorably to antiinflammatory therapy without reactivation of retinitis. Immune recovery vitritis may be the result of an immunologic reaction to latent CMV antigens in the eye in which T-lymphocytes play a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(35 citation statements)
references
References 15 publications
2
32
1
Order By: Relevance
“…It is still unclear why only some patients develop IRU. A recent study found that patients with more than 30% of retinal involvement with CMV retinitis were at the highest risk of developing IRU [14]. However, CMV genome was not detected in the aqueous humor, or vitreous, of the 5 participants of our study presenting IRU.…”
Section: Discussioncontrasting
confidence: 52%
“…It is still unclear why only some patients develop IRU. A recent study found that patients with more than 30% of retinal involvement with CMV retinitis were at the highest risk of developing IRU [14]. However, CMV genome was not detected in the aqueous humor, or vitreous, of the 5 participants of our study presenting IRU.…”
Section: Discussioncontrasting
confidence: 52%
“…IRU may cause vision loss from vitritis, retinal membrane formation, cystoid macular edema, or cataract. The larger the area of CMV retinitis, the greater the risk of both retinal detachment and IRU [23,24], again providing a compelling rationale for the benefit of early diagnosis and treatment.…”
Section: Diagnosis and Clinical Course Of CMV Retinitismentioning
confidence: 99%
“…The composition of the inflammatory cell infiltrate in the vitreous humor of patients with IRU was studied in three patients undergoing vitrectomy [71,99]. Immunohistochemical examination of the epimacular membrane showed a mixed cell population comprising 60% T-cells and <10% plasma cells [71].…”
Section: Immunopathogenesis Of Ird Associated With Infectious Agentsmentioning
confidence: 99%
“…The composition of the inflammatory cell infiltrate in the vitreous humor of patients with IRU was studied in three patients undergoing vitrectomy [71,99]. Immunohistochemical examination of the epimacular membrane showed a mixed cell population comprising 60% T-cells and <10% plasma cells [71]. In a different patient, the T-cell infiltrate contained a diverse population of CD8+ T-cells with most (57%) able to lyse CMV-infected fibroblasts, suggesting that they were CMV-specific cytotoxic T-cells [99].…”
Section: Immunopathogenesis Of Ird Associated With Infectious Agentsmentioning
confidence: 99%